Usefulness of the Neutrophil-to-Lymphocyte Ratio as a Predictor of Pneumonia and Urinary Tract Infection Within the First Week After Acute Ischemic Stroke - Gens, Robin; Ourtani, Anissa; De Vos, Aurelie; De Keyser, Jacques; De Raedt, Sylvie (Frontiers in Neurology, 2021)
Background: A high Neutrophil-to-Lymphocyte ratio (NLR) in patients with acute ischemic stroke (AIS) has been associated with post-stroke infections, but it’s role as an early predictive biomarker for post-stroke pneumonia (PSP) and urinary tract infection (UTI) is not clear. Aim: To investigate the usefulness of NLR obtained within 24 hrs after AIS for predicting PSP and UTI in the first week Methods: Clinical and laboratory data were retrieved from the University Hospital Brussels stroke database/electronic record system. Patients were divided into those who developed PSP or UTI within the first week after stroke onset and those who didn’t. Receiver operating characteristics (ROC) curves and logistic regression analysis were used to identify independent predictors. Results: 514 patients were included, of which 15.4% (n=79) developed PSP and 22% (n=115) UTI. In univariate analysis, NLR was significantly higher in patients who developed PSP (4.1 vs 2.8, p<0.001) but not in those who developed UTI (3.3 vs 2.9, p=0.074). Multiple logistic regression analysis for PSP showed that NLR, male gender, dysphagia and stroke severity measured by the National Institutes of Health Stroke Scale (NIHSS), were independent predictors of PSP. For NLR alone, the area under the curve (AUC) in the ROC curve was 0.66 (95% CI=0.59-0.73). When combining NLR ≥ 4.7 with age > 75 yrs, male gender, NIHSS > 7 and dysphagia, the AUC increased to 0.84 (95% CI=0.79-0.89). Conclusion: The NLR within 24 hrs after AIS appears to have no predictive value for post-stroke UTI, and is only a weak predictor for identifying patients at high risk for PSP. Its predictive value for PSP appears to be much stronger when incorporated in a prediction model including age, gender, NIHSS score and dysphagia.